Effect of using f three methods to develop flexibility among school age boxers (12-14 years) - Jabar, Abeduljaleel; Qusi, Mohammed (Journal of Physical Education, 2014)
By the fact that the researchers have supervised National Center training for the talent youth in boxing, as well as access to training program for some coaches, we noticed that their programs for flexibility was limiting to one kind, which is pressing on joins for many repetitions, so the researchers in this study used three methods of training have been applied to three groups: which they are stretching kinetic bouncing style, and stretching fixed style and contraction-relaxation stretching style. After conducting statistical methods the researchers concluded that the three styles have had a positive effect on the development of flexibility on sample research, and the contraction - relaxation stretching had the most effect than two styles are stretching kinetic bouncing style, and stretching fixed style. The researcher recommended suing these three styles training to develop flexibility on different samples from boxers in school age